Elevator pitch : [compact disc, unabridged] a novel - Barclay, Linwood (Harper Audio, 2019)
It all begins on a Monday, when four people board an elevator in a Manhattan office tower. Each presses a button for their floor, but the elevator proceeds, non-stop, to the top. Once there, it stops for a few seconds, and then plummets. Right to the bottom of the shaft. It appears to be a horrific, random tragedy. But then, on Tuesday, it happens again, in a different Manhattan skyscraper. And when Wednesday brings yet another high-rise catastrophe, one of the most vertical cities in the world, and the nation's capital of media, finance, and entertainment is plunged into chaos. Clearly, this is anything but random. This is a cold, calculated bid to terrorize the city. And it's working. Fearing for their lives, thousands of men and women working in offices across the city refuse to leave their homes. Commerce has slowed to a trickle. Emergency calls to the top floors of apartment buildings go unanswered.